2014
DOI: 10.1002/cphc.201402436
|View full text |Cite
|
Sign up to set email alerts
|

Computational Cogitation of Cn@Al12 Clusters

Abstract: A variety of novel Cn Al12 core-shell nanoclusters have been investigated using density functional calculations. A series of Cn cores (n=1-4) have been encapsulated by icosahedral Al12 , with characteristic physical properties (energetics and stabilities, ionisation energies, electron affinities) calculated for each cluster. Other isomers, with the Cn moiety bound externally to the Al12 shell, have also been studied. For both series, a peak in stability was found for n(C)=2, a characteristic that appears to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 83 publications
0
4
0
Order By: Relevance
“…However, we cannot exclude the possibility of other isomers, 12b­(O) and 12d­(I) , in which the C 2 unit is attached to a pentagonal bipyramidal Al 12 core and encapsulated by an icosahedral Al 12 cage, respectively, because their calculated AEA values are similar to the experimental values. The C 2 -encapsulated structure was theoretically predicted for neutral Al 12 C 2 …”
Section: Discussionmentioning
confidence: 93%
“…However, we cannot exclude the possibility of other isomers, 12b­(O) and 12d­(I) , in which the C 2 unit is attached to a pentagonal bipyramidal Al 12 core and encapsulated by an icosahedral Al 12 cage, respectively, because their calculated AEA values are similar to the experimental values. The C 2 -encapsulated structure was theoretically predicted for neutral Al 12 C 2 …”
Section: Discussionmentioning
confidence: 93%
“…Experimental studies of Al n C 5 –/0 ( n = 1–5) found that Al 5 C 5 – has a ptC structure and a star-like structure coexisting in the experiments . For carbon-doped aluminum clusters, several studies found that Al n C –/0 clusters with n = 3–5 have planar structures. Mass spectrometry and theoretical calculations indicated that Al 7 C – is a stable cage-like structure with resistance to oxidation, which can be viewed as a multiple valence superatom. Quantum chemistry calculations and photoelectron spectroscopy of Al 12 C –/0 suggested that neutral Al 12 C has a carbon-centered icosahedral structure while its anionic counterpart Al 12 C – has the carbon atom occupying a surface position. To provide more detailed information about the structural evolution of carbon-doped aluminum clusters, in this work, we investigated Al n C –/0 ( n = 6–15) clusters utilizing mass-selected anion photoelectron spectroscopy and theoretical calculations.…”
Section: Introductionmentioning
confidence: 99%
“…A series of small aluminum–carbon clusters have been investigated using anion photoelectron spectroscopy and theoretical calculations, and it was found that the Al 4 C – anion has a planar tetracoordinate carbon (ptC) structure with D 4h symmetry . In addition to the ptC structures, aluminum–carbon clusters were predicted to form many interesting structures such as planar pentacoordinate carbon structures, starlike structures, or carbon endohedral stable structures. In this work, we investigated the structures and chemical bonding of Al 4 C 6 –/0 clusters employing mass-selected anion photoelectron spectroscopy and first-principles theoretical calculations. Interestingly, it is found that the Al 4 C 6 – anion has a bowl-shaped distorted triangular structure and neutral Al 4 C 6 has a D 3h symmetry planar triangle-shaped structure.…”
Section: Introductionmentioning
confidence: 99%